Pemberian Tugas Dan Penguatan Guru Terhadap Peningkatan Prestasi Belajar Siswa SD Di Gugus VI Kecamatan Tallo Kota Makassar - Nashrullah, Nashrullah; Asdar, Asdar; Patandean, Agustinus Jarak (Jounal of Primary Education, 2023)
Penelitian bertujuan untuk mendeskripsikan hubungan antara pemberian tugas dengan prestasi belajar dan hubungan pemberian penguatan dengan prestasi belajar. Pendekatan penelitian yang digunakan adalah pendekatan kuantitatif. Populasi dalam penelitian ini adalah siswa SD kelas V di SD Gugus IV Kecamatan Tallo Kota Makassar. Sampel penelitian ini berjumlah 61 siswa. Teknik penarikan sampel menggunakan simple random sampling, Instrumen yang digunakan dalam penelitian ini adalah angket. Analisis data menggunakan software Statistikal Package for the Social Sciens (SPSS) versi 25. Hasil penelitian menunjukkan bahwa adanya hubungan significant antara pemberian tugas terhadap prestasi belajar (p-value 0,001) dan adanya hubungan signifikan antara pemberian penguatan terhadap prestasi belajar (p-value 0,001). This study aims to describe the relationship between giving assignments and learning achievement of elementary school students in Cluster VI Tallo District, Makassar City and the relationship between giving reinforcement and learning achievement of elementary school students in Cluster VI Tallo District, Makassar City. The research approach used was quantitative approach. The population in this study were fifth grade elementary school students Cluster IV Tallo District Makassar City. The sample of this study amounted to 61 students. The sampling technique used simple random sampling, the instrument used in this study was a questionnaire. Data analysis using software Statistical Package for the Social Sciens (SPSS) version 25. The results showed that there was a significant relationship between giving assignments to learning achievement (p-value 0.001) and there was a significant relationship between giving reinforcement to learning achievement (p-value 0.001) of elementary school students in Cluster VI Tallo District, Makassar City.